The Optimization of Ecobrick Plastic Waste Into Chairs and Tables at Hamu Pangia Orphanage, East Sumba - Tanahomba, Aprito Kapenga; Kalaway, Putri; Dillu, Adriana; Ghudi, Yandri Ngongo; Bunggih, Agustina Uru; Ndjoeroemana, Yohana; Bano, Vidriana Oktoviana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The increase in plastic waste every year requires proactive action to address this problem. The right strategy to implement is reducing waste, reusing and recycling waste. A concrete step for this problem is the production of ecobrick products. The aim of this service is to increase public awareness, especially for the children of the Hamu Pangia Orphanage, towards ecobrick products. This is deemed necessary as a call to protect or care about the environment in order to create a clean and healthy environment. Ecobricks have a positive impact on orphanage children by optimizing plastic waste and making it an alternative source of income. This PkM is carried out through counseling in the form of lectures and direct practice in making chairs and tables with orphanage children. Ecobrick products made in the form of chairs and tables are very useful for orphanage children. In conclusion, the orphanage children understand the importance of maintaining a clean and healthy environment by sorting waste properly.